PENGARUH PEMAHAMAN, KESADARAN WAJIB PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN PADA BADAN PENGELOLAAN PAJAK DAERAH KOTA PALEMBANG - Kurniawan, M. Orba; Aini, Dewi (Universitas Muhammadiyah Palembang, 2019)
This study aimed to determince the influence of Understanding, Taxpayers Awareness and Tax Sanctions on the Compliance Paying of Rural and Urban City and Building Tax in Regional Tax Management Office Palembang (Empirical Study in Kecamatan Plaju). The study was associative research The population of this study was taxpayers who live in the Kecamatan Plaju with the total was 11,149 taxpayers. The sample obtained was 92 taxpayers collected by the Slovin formula. The data used are primary and secondary data. Data collection methods used are the documentation method and the questionnaire method, Data analysis methods used were quantitative an qualitatif analysis. The results showed that Understanding, Taxpayers Awareness and Tax Sanctions gave significant influence on the Comliance Paying of Rural and Urban City Land and Building Tax in Regional Tax Management Office Palembang (Empirical Study in Kecamatan Plaju). The coefficient of determination showed that understanding, awareness of taxpayers, and tax sanctions was 54,2% while the remaining (45,8%) was influenced by other factors not included in this research model.